PENGARUH TAX KNOWLEDGE, TAX AWARENESS TERHADAP TAX COMPLIANCE WAJIB PAJAK (OP) - Gabby Imelda; Linda Santioso (Jurnal Paradigma Akuntansi, 2023)
This study aims to determine the effect of Tax Knowledge, Tax Awareness, towards Tax Compliance on 2)individual tax payers. 3). Sample was selected using a questionnaire method  and valid data 4)135 respondents. 5)Data processing techniques using 6)multiple regression analysis assisted by the SPSS ( Statistical Product and Service Solution) program for windows released 2 and Microsoft Excel 2013. 7) The results of this study indicate that Tax Knowledge, Tax Awareness, has a significant effect on Taxpayer Compliance (OP). 8) The implication of this research is the need to increase knowledge, awareness, tax laws so that the level of tax compliance increases so that it can have a positive effect on taxpayers, by increasing compliance, the benefits can also be felt around taxpayers.